Recurrence of Intravenous Talc Granulomatosis following Single Lung Transplantation - Richard C Cook; Guy Fradet; John C English; John Soos; Nestor L Müller; Thomas P Connolly; Robert D Levy (Canadian Respiratory Journal)
Advanced pulmonary disease is an unusual consequence of the intravenous injection of oral medications, usually developing over a period of several years. A number of patients with this condition have undergone lung transplantation for respiratory failure. However, a history of drug abuse is often considered to be a contraindication to transplantation in the context of limited donor resources. A patient with pulmonary talc granulomatosis secondary to intravenous methylphenidate injection who underwent successful lung transplantation and subsequently presented with recurrence of the underlying disease in the transplanted lung 18 months after transplantation is reported.